2023
DOI: 10.1111/acel.13815
|View full text |Cite
|
Sign up to set email alerts
|

The longevity response to warm temperature is neurally controlled via the regulation of collagen genes

Abstract: Studies in diverse species have associated higher temperatures with shorter lifespan and lower temperatures with longer lifespan. These inverse effects of temperature on longevity are traditionally explained using the rate of living theory, which posits that higher temperatures increase chemical reaction rates, thus speeding up the aging process. Recent studies have identified specific molecules and cells that affect the longevity response to temperature, indicating that this response is regulated, not simply … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We selected 6 upregulated collagen genes in circ- crh-1 (-) mutants (Knupp et al, 2022) and tested them in circ- crh-1 (-) mutants expressing Aβ 1-42 in muscle. We found that expression levels of the predicted cuticular collagen, col-49 , with a known role in lifespan regulation (Palani et al, 2023) and cuticular integrity (Jackson et al, 2014) was significantly increased, while the other tested collagen genes were not different from the GMC101 control. We do not yet know how loss of circ- crh-1 expression results in increased col-49 mRNA levels in the presence of muscle expressing Aβ 1-42 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We selected 6 upregulated collagen genes in circ- crh-1 (-) mutants (Knupp et al, 2022) and tested them in circ- crh-1 (-) mutants expressing Aβ 1-42 in muscle. We found that expression levels of the predicted cuticular collagen, col-49 , with a known role in lifespan regulation (Palani et al, 2023) and cuticular integrity (Jackson et al, 2014) was significantly increased, while the other tested collagen genes were not different from the GMC101 control. We do not yet know how loss of circ- crh-1 expression results in increased col-49 mRNA levels in the presence of muscle expressing Aβ 1-42 .…”
Section: Discussionmentioning
confidence: 78%
“…We hypothesized that the upregulation of cuticular collagen gene expression contributes to the amelioration of Aβ-induced toxicity in circ- crh-1 (-) mutants carrying the unc-54::A β 1-42 transgene. To test this hypothesis, from the 21 upregulated collagen genes previously identified in crh-1(syb385) mutants (Knupp et al, 2022), we selected six cuticular collagen genes of interest, including collagens that have a known association with lifespan such as col-49 and col-179 (Palani et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of collagens in C. elegans revealed a similar expression trend as in C. briggsae . Intertwined with the progression from reproductive to post-reproductive stage are also age-related effects on expression of certain collagen and cuticle-related genes that were reported to decline in older adults (Budovskaya et al, 2008; Ewald et al, 2015; Palani et al, 2023). Cuticular collagens have been found to confer resistance to pathogen infection and oxidative stress (Ewald et al, 2015; Sellegounder et al, 2019), which wane as animals age (Lopez-Otin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that although the epidermis plays a major role in synthesizing the cuticle, neurons can sense both the environment and tension to influence collagen dynamics [59]. In this regard, it was recently demonstrated that a neural G-protein coupled receptor, NPR-8, dynamically regulates collagen expression and cuticle structure in response to temperature changes and infection [48,60]. Furthermore, loss of npr-8 leads to increased resistance to pathogen infection [48].…”
Section: Discussionmentioning
confidence: 99%